Institutional logics and risk management practices in government entities: evidence from Saudi Arabia - Murr, Peter (IE University, 2022)
This study examines the adoption, implementation, and consequences of Risk Management (RM) practices by government entities in Saudi Arabia, a non-western, developing, and Islamictheocratic country. It investigates the dynamics behind the decision to change how government entities deal with risk and how this decision is put into practice in a dramatically different institutional context from those examined in prior research (e.g., Palermo, 2014). The study builds on the literature on institutional logics (Friedland and Alford, 1991; Lounsbury, 2008; Thornton and Ocasio, 2008; Thornton et al., 2012; Friedland, 2012). It adopts the cross-level model of institutional logics by Thornton et al. (2012) to clarify the interaction of potentially conflicting institutional logics. The institutional logics perspective provides a multi-level framework to examine the relationship between micro-processes at the individual level and a field’s institutional logics (Lounsbury, 2008). It represents a “general model of cultural heterogeneity unbiased toward the western world” (Thornton et al., 2012, p. 18) for understanding the adoption of practices. The empirical analysis is based on a longitudinal case study of a RM project implemented by a government entity. Data were obtained from interviews, observations, and documentary evidence. The adoption and implementation of RM were rooted in a traditional logic; even the catalyst of the government for adopting a RM culture across government entities was framed within a modernization reform program. The RM project led to an unstable situation; while the project used manifestations of a modernization logic, the actors’ actions were embedded in traditional logic. The study provides novel evidence of the adoption and implementation of RM in governmental entities in a developing, non-western country, which enriches accounts of drivers and barriers of RM, enhances knowledge about how managers struggle with competing logics, and addresses calls for a deeper understanding of the interplay between logics and managerial practices.
Lógicas institucionales y prácticas de gestión de riesgos en las entidades gubernamentales: análisis del caso de Arabia Saudí.
El presente estudio examina la adopción, la aplicación y las consecuencias de las prácticas de gestión de riesgos (GR) por parte de las entidades gubernamentales de Arabia Saudí, un país no occidental, en desarrollo y de corte teocrático-islámico. Investiga la dinámica que subyace a la decisión de cambiar la forma en que las entidades gubernamentales afrontan el riesgo y cómo esta decisión se aplica en un contexto institucional radicalmente distinto al examinado en investigaciones anteriores (por ejemplo, Palermo, 2014). El estudio se basa en la literatura sobre lógica institucional (Friedland y Alford, 1991; Lounsbury, 2008; Thornton y Ocasio, 2008; Thornton et al., 2012; Friedland, 2012). En concreto, se adopta el modelo de lógicas institucionales de Thornton et al. (2012) para examinar la interacción de lógicas institucionales potencialmente conflictivas. La perspectiva de las lógicas institucionales proporciona un marco multinivel para examinar la relación entre los procesos a escala individual y las lógicas institucionales de un campo (Lounsbury, 2008). Este enfoque se caracteriza por representar un “modelo general de heterogeneidad cultural no sesgado hacia el mundo occidental” (Thornton et al., 2012, p. 18) que es útil para comprender la adopción de prácticas. El análisis empírico se basa en un estudio de caso longitudinal de un proyecto de GR ejecutado por una entidad gubernamental del Arabia Saudí. Los datos se obtuvieron a partir de entrevistas, observaciones y pruebas documentales. Los resultados sugieren que la adopción y la aplicación de la GR estaban arraigadas en una lógica tradicional, aunque el catalizador del gobierno para adoptar una cultura de GR en todas las entidades gubernamentales se enmarcaba en un programa de reformas modernizadoras (lógica de modernización). El proyecto de GR condujo a una situación inestable; si bien el proyecto utilizó manifestaciones de una lógica de modernización, las acciones de los actores se enmarcaron en la lógica tradicional. El estudio aporta evidencia novedosa sobre la adopción y la aplicación de la GR en las entidades gubernamentales de un país en desarrollo y no occidental, lo que enriquece nuestro conocimiento sobre los estímulos y las barreras para la adopción de sistemas de GR y sobre la forma en que los gestores afrontan lógicas institucionales que compiten entre sí, y responde a la necesidad de más investigación sobre la interacción entre las lógicas institucionales y las prácticas de gestión.
Keywords: Risk management; Government entities; Institutional logics; Saudi Arabia; 5311 Organización y Dirección de Empresas; 5909 Administración Pública; 11 Lógica